PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT. SEMEN TONASA KABUPATEN PANGKEP - Idris, Nurhikma (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
The objective of this study is to determine the effect of brand image and product quality on purchasing decisions at PT. Semen Tonasa, Pangkep. The data collection techniques used in this study are observation, interviews, and questionnaires. The sample in this study amounted to 99 respondents including 94 employees of PT. Semen Tonasa distributed questionnaires and 5 consumers/users were interviewed directly. The data analyzed used Multiple Linear Regression Analysis with Hypothesis Testing, Determination Test, and t-Test. data management tool using SPSS version 22.0. based on the results of research that has been done. shows that, Brand Image has a partial effect on purchasing decisions at Pt. Semen TonasaPangkep Regency, product quality has a partial effect on purchasing decisions at PT. Semen TonasaPangkep Regency, and Brand Image and Product Quality have a Simultaneous effect on Purchase Decisions at PT. Semen TonasaPangkep Regency.